Rheumatic diseases in the Corpus Hippocraticum - G. Squillace (Reumatismo, 2011)
Medecine of V and IV centuries B.C. attested in the Corpus Hippocraticum ascribes all diseases to the rheuma, i.e. the flux of humours into the body. This flux produces not only the rise of cold, hoarsness, cough, reddenings, dropsy, but also arthritis, sciatica, gout.